Estimation of inbreeding effect on conception in Czech Holstein - Hofmannová, Michala; Přibyl, Josef; Krupa, Emil; Pešek, Petr (Czech Journal of Animal Science, 2019)
The influence of calculated inbreeding coefficients on the conception of heifers and cows was analysed by a two-trait binary model for conceived/not conceived after each insemination on 677 234 Czech Holstein cows and heifers with 3 248 299 insemination records as the covariable in a statistical model. The data between 1996 and 2014 were analysed. Various effects and their statistical influence on traits were tested by a generalized linear model. Consequently, genetic parameters were estimated by the Gibbs sampling method and used in predicting breeding values using the best linear unbiased prediction by animal model (BLUP-AM). The mean for the conception rate of cows averaged over lactations was 33.7% and for heifers it reached 53.8%. Average inbreeding coefficient increased from 1% in 1996 to almost 5% by 2013 and was in the range of 0-45%. The rate of inbreeding per generation was 0.20%. Although the effect of inbreeding was statistically significant (P = 0.05) for both traits, the proportion of variability explained by the models was relatively low. Estimated genetic parameters were low for both traits. Coefficient of heritability was 2.00% and 1.30% for cows and heifers, respectively, whereas coefficients of repeatability reached 6.09% and 7.08% for cows and heifers, respectively. The random effect of the permanent environment (PE) reached higher values than the additive genetic variance (G) and explained 5.67% and 4.09% of variability for cows and heifers, respectively. A negative impact of inbreeding on heifer and cow conception was observed, whereby every 10% increase in inbreeding coefficient resulted in a conception decline by 2.23%. Calculated Spearman's rank correlation coefficient between estimated breeding values considering and not considering the effect of inbreeding was close to one. Presented results indicate that inbreeding has a negligible influence on the breeding values of conception. The results also indicate that it is not necessary to include inbreeding coefficient in the routine breeding value evaluation of conception rate of heifers and cows. On the other hand, monitoring of inbreeding is necessary to avoid an increase of its rate.
Keywords: BLUP; breeding value; dairy cattle; Gibbs sampling; inbreeding depression